From Liverpool to New York City: behind the veil of a Black British male scholar inside higher education. Issue 3 (4th May 2017) - Christian, Mark
Abstract: This paper speaks to the experience of Black British male experience in academia, with emphasis on UK and US colleges and universities. It is an autoethnographic study in terms of relating, witnessing, and noting both learning and teaching experiences within the confines of higher education in the UK and US. The idea behind this paper is to highlight the need for greater access and opportunity for Black scholars to teach and study without stress and strain on their minds and bodies. There are a number of studies that confirm the efficacy in sharing one's experience as an 'insider' within academia as a person of color. But there are few studies that speak directly to the reality of teaching and researching within the context of Africana or Black Studies in higher education. It is noted that academia should be a place whereby liberal arts of all genres are accepted and respected; in this sense, there is still a long way to go before we can attest to the affirmative of this point of view.